Hedonic Adaptation to Treatment: Evidence from a Medical Intervention. Issue 3 (3rd March 2020) - Barazzetta, Marta; Appleton, Simon; Owens, Trudy
Abstract: We investigate whether changes in life circumstances lead to long-lasting changes in subjective well-being using a medical intervention that provided orthotic equipment to Ugandan adults with lower limb disabilities. The intervention had a positive effect on mobility and physical health, and treated patients reported a significant improvement in life satisfaction in the first few months after the treatment. However, the effect on subjective well-being was not prolonged. After one year, life satisfaction returned to the pre-treatment levels. The evidence of adaptation is also supported by evidence of changes in patients' reference levels, in the form of aspirations measured as both the level of income considered sufficient to live well, and the minimum income to make ends meet.